2021
DOI: 10.11130/jei.2021.36.4.689
|View full text |Cite
|
Sign up to set email alerts
|

Economic Globalization, Entrepreneurship, and Inclusive Growth in Africa

Abstract: An increasing number of studies are examining the relationship between entrepreneurship and growth. This relationship is controversial, especially for developing countries. Recent improvements in economic growth have led to a focus on growth inclusiveness, which spreads economic opportunities throughout a society. However, studies that focus on the role of entrepreneurship in inclusive growth remain scarce. To fill that gap, this study investigates the dynamic relationship between economic globalization, entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 75 publications
(98 reference statements)
1
19
0
1
Order By: Relevance
“…In the African entrepreneurial environment, studies suggest that it involves all factors affecting entrepreneurial activities including innovation, creativity, financial and inherent risks (Ajide, 2020; Ajide et al , 2021). A large number of African economies reform their administrative procedures targeting and encouraging small business creation.…”
Section: Overview Of Economic Complexity and Entrepreneurial Environm...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the African entrepreneurial environment, studies suggest that it involves all factors affecting entrepreneurial activities including innovation, creativity, financial and inherent risks (Ajide, 2020; Ajide et al , 2021). A large number of African economies reform their administrative procedures targeting and encouraging small business creation.…”
Section: Overview Of Economic Complexity and Entrepreneurial Environm...mentioning
confidence: 99%
“…However, the statistics reveal that some selected female entrepreneurs are being driven by necessity. Just like other developing regions, African innovation levels remain low (Dvouletý and Orel, 2019; Ajide et al , 2021). This probably gives an insight that the level of economic complexity is not too higher compared to developed nations.…”
Section: Overview Of Economic Complexity and Entrepreneurial Environm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed the positive impact of entrepreneurship [ 15 ], especially female entrepreneurship [ 67 , 68 ], on inclusive economic growth. The process of entrepreneurship can not only increase the income of entrepreneurs and reduce poverty, but it also provides employment opportunities and reduces the unemployment rate.…”
Section: Characteristics Of Ig and Plausible Explanatory Variables Fo...mentioning
confidence: 75%
“…Further, in studying the key drivers of IG, scholars mostly use traditional econometric models and draw different conclusions. For instance, Whajah et al [ 14 ] used a fixed effect regression model to examine the relationship between government size, public debt, and IG for a panel of 54 African countries, and found that the former has a positive effect on IG, while the later has a negative effect on IG; Ajide et al [ 15 ] investigated the dynamic relationship between economic globalization, entrepreneurship, and IG using panel econometrics; Biswas et al [ 10 ] proposed foreign direct investment and trade liberalization fostering greater inclusiveness, while financial deepening and technological change have no discernible effect; Kouton [ 16 ] examined the role of trade facilitation measures in lowering barriers to trade and raising incomes and promoting IG. Furthermore, Kang and Martinez-Vazquez [ 17 ] examined the conditions under which the FDI can effectively lead to IG using a fixed effects regression; Oyinlola et al [ 18 ] explored the relationship between human capital, innovation, and IG by the fixed effects model; Seven [ 19 ] employed a series of econometric models to study the relation between financial development and income inequality.…”
Section: Introductionmentioning
confidence: 99%